Long‐term follow up of HIV‐1‐infected Korean haemophiliacs, after infection from a common source of virus. (January 2015) - Kim, B.‐R.; Kim, J.‐E.; Sung, H.; Cho, Y.‐K.
Summary In the early 1990s, 20 haemophiliacs (HPs) were infected with a common source of HIV‐1 viruses through the contaminated clotting factor IX. The aim of this study is to review 20 HPs infected with a common source of virus. The enrolled patients have been consecutively treated with Korean red ginseng (KRG), zidovudine (ZDV) or two‐drug therapy and highly active antiretroviral therapy (HAART). We determined full‐length pol gene over 20 years and human leukocyte antigen (HLA) class I with peripheral blood mononuclear cells and reviewed medical records. Eighteen HPs experienced various opportunistic infections or clinical manifestations. There were significant inverse correlations between the HLA prognostic score and the annual decrease in CD4+ T‐cell counts prior to HAART (AD) (P < 0.05) and the amount of KRG and the AD (P < 0.01). From 1998, the HPs had been treated with HAART. Each of the two patients died without and with HAART regimen respectively. At present, 16 HPs have been alive with HAART. Among the 16 HPs, 12 and 4 are on HAART‐plus‐KRG and HAART only respectively. Eleven HPs including 2 HPs with G‐to‐A hypermutations had revealed resistance mutations. Ten and two HPs have shown poor adherence and incomplete viral suppres‐sion on HAART respectively. Virological failure based on WHO guidelines was not observed on KRG‐plus‐HAART. Two HPs revealed additional resistance mutations against two classes on KRG‐plus‐HAART. As a nationwide study, we first report overall features on clinical course of Korean haemophiliacs. Further education on the importance of drug adherence is needed.